PENGARUH RETURN ON EQUITY, DEBT TO ASSET RATIO, DAN CURRENT RATIO TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG LISTING DI BEI PERIODE 2013-2018 - Sanjaya, Ganda; Ariesa, Yeni (JEBIM Prima, 2020)
The industrial sector is currently one of sectors that is able to accelerate economic growth. Because this sector has a role in overcoming problem of unemployment and creating an economy based on natural resources. Therefore, this sector supports national economic growth (www.economy.okezone.com). This study aims to examine and analyze influence of Return on Equity, Debt to Asset Ratio, and Current Ratio on Dividend Policy in basic and chemical industry companies listed in Indonesia Stock Exchange period 2013-2018. Processing data with SPSS 22 Software. Data analysis method used is descriptive statistics, classical assumption test, multiple linear regression analysis and hypothesis testing (simultaneous test, partial test and coefficient of determination). The results of study prove simultaneously Return On Equity, Debt to Asset Ratio and Current Ratio significantly influence Dividend Policy with F value of 15,641. Partially Return On Equity partially has no significant effect on Dividend Policy with t value of -3,378, Debt to Asset Ratio partially has positive and significant effect on Dividend Policy with t value of 4,611, Current Ratio partially has positive and significant effect on Policy Dividends with t value of 5,400, with a coefficient of determination of 36.3%. The remaining 63.7% is the influence of other variables.